Efektivitas penerapan teknik pemasangan nasogastric tube berbasis sensor pada pasien stroke infark dalam praktik keperawatan: A systematic review - Purnomo, Dedy Miswar; Mulyono, Wastu Adi; Nani, Desiyani (Holistik Jurnal Kesehatan, 2026)
Background: Nasogastric tube (NGT) placement is an important intervention in meeting the nutritional needs of stroke patients with dysphagia. However, conventional methods often have limitations in accuracy and risk complications such as aspiration, pneumonia, and misplacement into the airway. Advances in sensor technology have improved the accuracy and safety of NGT placement procedures, thereby minimizing clinical risks and enhancing the effectiveness of nursing practices. Purpose: To determine the effectiveness of implementing sensor-based nasogastric tube insertion techniques in infarction stroke patients in nursing practice. Method: This study used a systematic review design based on the PRISMA guidelines with the PICOS framework. Articles were searched on SCOPUS, PubMed, ScienceDirect, Scisapse, and Elicit, with inclusion criteria of articles from the last 10 years, Quasi-Experimental design, RCT, Quantitative Research, and R&D. From the selection and screening process, nine articles that met the criteria were obtained and analyzed using a narrative approach. Results: Sensor technology, including pressure sensors, magnetic sensors, warning sensors, fog computing, and color detection sensors, consistently improves the accuracy of NGT position detection, speeds up the verification process, and reduces the risk of dislodgement and misalignment. Several studies have shown position tracking accuracy to reach a deviation of only 0.55–1.63 cm compared to the gold standard of radiology, while R&D research has demonstrated excellent user acceptance with validation >89%. Sensor technology also improves patient safety and provides real-time feedback unavailable with conventional methods. Conclusion: The application of sensor-based NGT placement techniques has been proven effective in improving the accuracy, safety, and efficiency of NGT placement in stroke patients. This technology has the potential to become the standard for supporting clinical processes in the future, although further research is needed on costs, facility readiness, and device integration into nursing practice.   Keywords: Nasogastric Tube; Nursing Practice; Sensor-Based Technique; Stroke Infarction.   Pendahuluan: Pemasangan nasogastric tube (NGT) merupakan intervensi penting dalam pemenuhan kebutuhan nutrisi pasien stroke infark dengan disfagia. Namun, metode konvensional sering memiliki keterbatasan akurasi dan berisiko menimbulkan komplikasi, seperti aspirasi, pneumonia, hingga misplacement ke saluran napas. Perkembangan teknologi sensor memungkinkan peningkatan akurasi dan keamanan prosedur pemasangan NGT, sehingga meminimalkan risiko klinis serta meningkatkan efektivitas praktik keperawatan. Tujuan: Untuk mengetahui efektivitas penerapan teknik pemasangan nasogastric tube berbasis sensor pada pasien stroke infark dalam praktik keperawatan. Metode: Penelitian systematic review berdasarkan pedoman PRISMA dengan framework PICOS. Pencarian artikel dilakukan pada SCOPUS, PubMed, ScienceDirect, Scisapse, dan Elicit, dengan kriteria inklusi artikel 10 tahun terakhir, desain quasi experimental, RCT, quantitative research, dan R&D. Dari proses seleksi dan penyaringan, diperoleh 9 artikel yang memenuhi kriteria dan dianalisis menggunakan pendekatan naratif. Hasil: Teknologi sensor, termasuk sensor tekanan, sensor magnetik, warning sensor, fog computing, hingga sensor pendeteksi warna secara konsisten meningkatkan akurasi deteksi posisi NGT, mempercepat proses verifikasi, dan mengurangi risiko dislodgement maupun salah jalur. Beberapa studi menunjukkan akurasi pelacakan posisi mencapai deviasi hanya 0.55–1.63 cm dibandingkan gold standard radiologi, sementara penelitian R&D menunjukkan penerimaan sangat baik pada pengguna dengan validasi >89%. Teknologi sensor juga meningkatkan keselamatan pasien dan memberikan real-time feedback yang tidak tersedia pada metode konvensional. Simpulan: Penerapan teknik pemasangan NGT berbasis sensor terbukti efektif meningkatkan akurasi, keamanan, dan efisiensi pemasangan NGT pada pasien stroke infark. Teknologi ini berpotensi menjadi standar pendukung proses klinis di masa mendatang, meskipun diperlukan penelitian lanjutan mengenai biaya, kesiapan fasilitas, dan integrasi perangkat dalam praktik keperawatan.   Kata Kunci: Nasogastric Tube; Praktik Keperawatan; Stroke Infark; Teknik Berbasis Sensor.